Making Place : Space and Embodiment in the City - Sen, Arijit, 1963- (Book collections on Project MUSE., 2013)
Space and place have become central to analysis of culture and history in the humanities and social sciences. Making Place examines how people engage the material and social worlds of the urban environment via the rhythms of everyday life and how bodily responses are implicated in the making and experiencing of place. The contributors introduce the concept of spatial ethnography, a new methodological approach that incorporates both material and abstract perspectives in the study of people and place, and encourages consideration of the various levels-from the personal to the planetary-at which.